2007
DOI: 10.1007/s00384-007-0350-7
|View full text |Cite
|
Sign up to set email alerts
|

Health economic evaluation of ferucarbotran-enhanced MRI in the diagnosis of liver metastases in colorectal cancer patients

Abstract: In this comparative medical decision analysis, it was shown that ferucarbotran-enhanced MRI has the potential to improve medical management and save health care costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…Relatively few comparable studies on health-economic aspects of contrast agents in liver disease seem to have been published [4,[23][24][25][26]. These have shown that contrastenhanced MRI has the potential to improve medical management and save health-care costs compared with contrast-enhanced CT, mainly due to the avoidance of unnecessary surgical procedures.…”
Section: Confirmed Surgical Plan Modified Surgical Plan No Resectionmentioning
confidence: 98%
See 2 more Smart Citations
“…Relatively few comparable studies on health-economic aspects of contrast agents in liver disease seem to have been published [4,[23][24][25][26]. These have shown that contrastenhanced MRI has the potential to improve medical management and save health-care costs compared with contrast-enhanced CT, mainly due to the avoidance of unnecessary surgical procedures.…”
Section: Confirmed Surgical Plan Modified Surgical Plan No Resectionmentioning
confidence: 98%
“…The findings from the study indicated that Teslascan® MRI was more sensitive than contrast-enhanced CT in the preoperative prediction of the resectability of hepatic lesions, which leads to cost savings, as many cases of unnecessary surgery could be avoided. In a recent study by Annemans et al [4], the healtheconomic impact of ferucarbotran-enhanced MRI in the diagnosis of hepatic colorectal cancer metastases was investigated. A decision-tree comparing diagnosis based on contrast-enhanced spiral CT with ferucarbotran-enhanced MRI was constructed.…”
Section: Confirmed Surgical Plan Modified Surgical Plan No Resectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the setting of hepatic imaging, MRI is still widely regarded as a problem‐solving modality in case of equivocal findings on CT or ultrasound imaging, rather than a first‐line imaging modality. However, depending on the number of unclear cases, this might result in an overall increased number of imaging procedures for patients as well as suboptimal use of resources.…”
Section: Introductionmentioning
confidence: 99%
“…As SPION are magnetic, they can also be used as a contrast agent in MRI for disease diagnosis and treatment monitoring. In fact, several SPION formulations have been approved for clinical use including dextran-coated iron oxide (Feridex ® ) for liver and spleen imaging, and ferumoxytol for iron replacement therapy [83, 84]. SPIONs are safe and stable nanodelivery system to carry genes, including small interfering RNA (SiRNA), nucleic acids and plasmid DNA [8587], as well as chemotherapy and proteins [8890].…”
Section: Nanomedicine In Therapeuticsmentioning
confidence: 99%